Radial Variation in Growth Ring Widths with Reference to Age from Juvenile Wood to Mature Wood of Five Selected Indian Woods - Sharma, Upasna; Gupta, Sangeeta; Yadav, Ronak (Indian Forester, 2024)
Trees are diverse in terms of growth rate. From fastest growing tree species such as Poplar to slowest growing tree species like white Cedar; growth rate varies widely among trees. Furthermore, the growth rate differs within a tree in juvenile wood and mature wood. Cambium and favorable climatic conditions are the two major factors responsible for the growth of a tree. The paper focuses on the growth rate or radial variation in growth ring widths from pith to bark of five wooden discs of Indian woods. Among the studied samples; Cedrela microcarpa was found to be fastest growing tree species with an average annual growth of 5.01 mm followed by Tectona grandis and Ulmus wallachiana with an average annual growth of 3.37 mm and 3.05 mm respectively. Least average growth was found for Robinia pseudoacacia (2.19 mm) and Tsuga brunoniana (2.36 mm). Correlation between ring width and age of the tree has also been developed. Accordingly, a weak negative correlation exists between two variables for two discs (Tectona grandis and Robinia pseudoacacia) while there exist no relation or very weak relation between ring width and age for another three discs i.e., Cedrela microcarpa, Tsuga brunoniana and Ulmus wallichiana. The cambial activity could be declared higher in initial phase of tree and ring growth was observed more or less environmental dependent.